Propuesta de un programa de educación ambiental para mejorar la calidad del aire en la ciudad de Loja - Reátegui Betancourt, José Jaime (2015)
In the last years, air pollution in city of Loja is an environmental problem caused by rapid population and urban growth. This research tries to improve air quality through the following objectives: first, to systematize information of environmental pollution problems that impair air quality in the city of Loja; and second, to establish a proposed environmental education program to raise awareness of the population and contribution to improving air quality in city of Loja. To accomplish the first objective, a basic and solid literature review of studies of air quality of Loja supported this study. This study, also present a proposed Environmental Education Program as a tool of environmental policy. To fulfill the second objective, this proposal focus to help the public to know and raise awareness of environmental problems increasing learning ability, behavior change and participation in decision-making to solve the problems of air pollution. As a result, this investigation found that most problems that impair air quality in the city of Loja are CO2 pollution increased by 23 % over the last three years; generating high sound pressure levels averaged 62 dB exceeding the limits set in TULSMA. The pollution caused by Particulate Matter PM2.5 ranges from 37 ug/m3 and 66 ug/m3, it exceeds the limits permitted in the TULSMA; also, the concentration of PM10 reaches levels that ranges from 54 ug/m3 to 81 ug/m3; despite, it seems high, it does not exceed the established limits. However, for the coming years this levels may be higher, the main source is caused by motor vehicles. Likewise, in the Environmental Education Programme two projects aimed to train all the involved actors in Environmental Management, such as managers of industries, public transport unions, chamber of commerce and education levels students, communication, and dissemination to the public on mitigation measures to improve air quality in city of Loja.